Good trouble how deviants, criminals, heretics, and outsiders have changed the world for the better - Wolf, Brian Christopher (Lexington Books, 2019)
This book argues that some of the most important deviants have been at the forefront of positive social change and the creation of a more just, fair, and humane society.